Sintering of oxide and carbide ceramics by electron beam at forevacuum pressure; IOP Conference Series: Materials Science and Engineering; Vol. 116 : Advanced Materials and New Technologies in Modern Materials Science - Dvilis E. S. Edgar Sergeevich; Tolkachev O. S. Oleg Sergeevich; Burdovitsin V.; Khasanov A. O. Aleksey Olegovich; Petyukevich M. S. Mariya Stanislavovna (2016, 2016)
Title screen